Future insight to enhance the role of the university in reinforcing patriotism among impaired students from their view point - Al-Qahtani, Abdullah bin Hijab (Journal of Educational and Psychological Sciences, 2021)
The current study aimed to reach a theoretical framework of knowledge that enables decision-makers, specialists and experts to define the planning, coordination and innovative roles that the university can play to enhance the national belonging of people with disabilities. The sample of the study consisted of (150) university students with disabilities (visual, auditory, and kinesthetic), who were taken through a comprehensive social survey, which is a descriptive analytical study using the comprehensive social survey approach, and the Statistical Package for Social Sciences program was used. (SPSS) version (18) in the statistical analysis of the study tool, and scientific and practical results were reached by answering questions, and based on the theoretical framework and those results, a number of recommendations were proposed.